Pengaruh Kultur Teknis terhadap Serangan Hama Spodoptera litura pada Tanaman Kubis (Brassica oleracea) di Desa Kerinjing Kecamatan Dempo Utara Kota Pagar Alam Provinsi Sumatera Selatan: Effects of Cultural Technique on The Infestation of Spodoptera litura on Cabbage (Brassica oleracea) Cultivation in Village Kerinjing District Dempo Utara City of Pagar Alam, South Sumatra - Arsi Arsi; Rahmat Akbar Aziz (Politeknik Negeri Lampung, 2021)
ABSTRACT Cabbage is one of vegetable crop belongs to Genus Brassica, a member of Family Cruciferae (Brassicaeae). The crop is originally from subtropical areas and has long been cultivated in Indonesia. Crop landscape ecosystem is very dynamic, both of its biotic and abiotic factors. Plant disturbing organism is an obstacle and production limiting factor in Indonesia either fir food crops, horticultural crops or estate crops. Inter cropping is cropping pattern cultivating more than one crop species in an area at the same time. Intercropping is one of efforts in agriculture intensification program to optimize crop production and maintain soil fertility. The objective of this field study was to know the effects of cultural technique on pest infestation on cabbage cultivation in Village Kerinjing, Sub district Dempo Utara, City of Pagar Alam. Observation method applied was conducted using purposive sampling method. Data collected was primary data in the form of damage intensity and secondary data collected by interviewing farmers. Based on the analysis of weekly data of damage intensity of three different cabbage cultivations in Village Kerinjing, there was no significant difference among the tree cultivations. Keywords: Pest, Cabbage Crop, Cultural Technique